Re-Voting for The Election of Regents and Deputy Regents (Analysis Study of The Constitutional Court Decision Number: 58/Php. Bup-Xix/2021 Siyasah Qadhaiyah Perspective) - Ramsah; Zaid al Fauza Marpaung (Journal Equity of Law and Governance, 2024)
This study aims to conduct an in-depth analysis of the Constitutional Court Decision No. 58/PHP.BUP-XIX/2021, which ordered a re-vote in the 2020 Labuhanbatu Regent and Deputy Regent Election, from the perspective of Siyasah Qadhaiyah (Islamic judicial politics). The focus of this research is to examine how the Constitutional Court's decision can be understood within the framework of Islamic legal principles, such as justice (‘adl), responsibility (amanah), and public interest (maslahah), and to assess whether the ruling aligns with or deviates from the concept of Fiqh Siyasah Qadhaiyah. The main question addressed in this study is whether the Constitutional Court’s action in ordering a re-vote adheres to Siyasah Qadhaiyah principles, particularly in ensuring justice, transparency, and accountability in the electoral process. Using a normative approach by reviewing both Indonesian positive law and Fiqh Siyasah Qadhaiyah literature, this study also explores how Islamic principles can be applied in a modern context to safeguard the integrity and fairness of the democratic process. By employing judicial decision analysis, the research aims to understand the impact of the Constitutional Court’s ruling on the protection of voters' rights and its contribution to the enforcement of substantive justice in elections. The results of this study are expected to provide theoretical contributions to the development of Islamic legal thought in relation to modern legal systems, particularly in resolving regional election disputes in Indonesia.